2015
DOI: 10.1001/jama.2015.280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varenicline on Smoking Cessation Through Smoking Reduction

Abstract: Importance Some cigarette smokers may not be ready to quit immediately but may be willing to reduce cigarette consumption with the goal of quitting. Objective To determine efficacy and safety of varenicline for increasing smoking abstinence rates through smoking reduction. Design, Setting, and Participants Randomized, blinded, placebo-controlled, multinational clinical trial with a 24-week treatment period and 28-week follow-up conducted between July 2011 and July 2013 at 61 centers in 10 countries. 1510 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(73 citation statements)
references
References 29 publications
2
66
2
3
Order By: Relevance
“…After the removal of duplicates and screening of titles and abstracts, 68 trials underwent full‐text review. In total, 38 RCTs met all eligibility criteria and were included in our meta‐analysis 10, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates and screening of titles and abstracts, 68 trials underwent full‐text review. In total, 38 RCTs met all eligibility criteria and were included in our meta‐analysis 10, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] Varenicline is an α4β2 nicotinic acetylcholine receptor partial agonist that reduces cravings and withdrawal symptoms during smoking abstinence and also decreases the reinforcing effects of nicotine. 8 Although varenicline has been shown to be effective for smoking cessation in both healthy smokers and patients with stable cardiovascular disease, [9][10][11] little is known about its efficacy in patients with acute cardiovascular disease. For this reason, we assessed the efficacy of varenicline in a high risk patient population of smokers hospitalized with ACS.…”
mentioning
confidence: 99%
“…Varenicline is generally administered for 12 weeks, although it is important to consider that two studies have shown that treatment prolongation to 24 weeks is safe and can increase success rate [7,8]. The number needed to treat with varenicline to obtain a favourable outcome, based on weighted average rates, is 11 (95% IC: 9-13) [9].…”
Section: Results Abstinence From Smokingmentioning
confidence: 99%
“…The schedule of visits for each participant were as follows: at baseline, at 2,4,8,12,16,20,24 weeks and additionally at 9 and 12 months. Also, there were two telephone calls at 8 th and 20 th weeks.…”
Section: Procedures and Interventionsmentioning
confidence: 99%